An observational study to evaluate three pilot programmes of retesting chlamydia-positive individuals within 6 months in the South West of England. Issue 10 (28th October 2015) - Angel, Georgina; Horner, Paddy J; O'Brien, Norah; Sharp, Matt; Pye, Karl; Priestley, Cecilia; Macleod, John; Looker, Katharine J; Turner, Katherine M E
Abstract : Objectives: To evaluate 3 pilot chlamydia retesting programmes in South West England which were initiated prior to the release of new National Chlamydia Screening Programme (NCSP) guidelines recommending retesting in 2014. Methods: Individuals testing positive between August 2012 and July 2013 in Bristol (n=346), Cornwall (n=252) and Dorset (n=180) programmes were eligible for inclusion in the retesting pilots. The primary outcomes were retest within 6 months (yes/no) and repeat diagnosis at retest (yes/no), adjusted for area, age and gender. Results: Overall 303/778 (39.0%) of participants were retested within 6 months and 31/299 (10.4%) were positive at retest. Females were more likely to retest than males and Dorset had higher retesting rates than the other areas. Conclusions: More than a third of those eligible were retested within the time frame of the study. Chlamydia retesting programmes appear feasible within the context of current programmes to identify individuals at continued risk of infection with relatively low resource and time input.